Buddhist Higher Learning Horizon and Its Relation to Global Trends : The Trajectory of Global Buddhist Pedagogy - Jovini Jovini; Julia Surya; Sri Utami (Universitas Pendidikan Mandalika, 2024)
This study aims to dissect the challenges, identify the unique characteristics, and propose viable strategies for the seamless integration of local and global dimensions in higher Buddhist education. This study used the systematic literature review method with a qualitative approach. The research hinged on an extensive review of scholarly articles, primary texts, and reports on Buddhist education in Indonesia and internationally and then analyzed using thematic analysis. Results highlight that Indonesian Buddhist education possesses unique characteristics and mirrors global patterns, albeit with localized interpretations. The study underscored the importance of recognizing and integrating the Buddhayana spirit amidst global Buddhist sectarian diversities. The contribution of this review was twofold: first, it enriches the understanding of the specificities of Indonesian Buddhist higher education and its relation to global trends; second, it advocates for a harmonious blend of local and global in shaping the trajectory of global Buddhist pedagogy.